Extracellular Vesicles: Emerging Roles in Developing Therapeutic Approach and Delivery Tool of Chinese Herbal Medicine for the Treatment of Depressive Disorder - Wu, Qian; Duan, Wen-Zhen; Chen, Jian-Bei; Zhao, Xiao-Peng; Li, Xiao-Juan; Liu, Yue-Yun; Ma, Qing-Yu; Xue, Zhe; Chen, Jia-Xu (Frontiers in Pharmacology, 2022)
Extracellular vesicles (EVs) are lipid bilayer-delimited particles released by cells, which play an essential role in intercellular communication by delivering cellular components including DNA, RNA, lipids, metabolites, cytoplasm, and cell surface proteins into recipient cells. EVs play a vital role in the pathogenesis of depression by transporting miRNA and effector molecules such as BDNF, IL34. Considering that some herbal therapies exhibit antidepressant effects, EVs might be a practical delivery approach for herbal medicine. Since EVs can cross the blood-brain barrier (BBB), one of the advantages of EV-mediated herbal drug delivery for treating depression with Chinese herbal medicine (CHM) is that EVs can transfer herbal medicine into the brain cells. This review focuses on discussing the roles of EVs in the pathophysiology of depression and outlines the emerging application of EVs in delivering CHM for the treatment of depression.